Identifikasi Kandungan Logam Timbal (Pb) Pada Buah Nangka (Artocarpus Heterophyllus) Di Media Jalan Kota Bandar Lampung - Rama Wicaksa; Agus Setiawan; Slamet Budi Yuwono; Samsul Bakri (Jurnal Penelitian Pertanian Terapan, 2018)
Lead (Pb) is a heavy metal that naturally exists in the earth's crust and diffuses in small amounts through natural and artificial processes. This study aims to determine the amount of lead contained in the fruit jackfruit (Artocarpus heterophyllus) in the median street Bandar Lampung City. To know the factors that affect the lead content of jackfruit (Artocarpus heterophyllus) is done regression analysis. Research shows that the lead content of the jackfruit (Artocarpus heterophyllus) in the median of Bandar Lampung City road has exceeded the consumption limit, besides the factors affecting the lead content of the jackfruit (Artocarpus heterophyllus) to be the tree season, the geometry of the bend, the topography of the incline and the derivative.